Hubungan Tingkat Pengetahuan Gizi Ibu Hamil dengan Taksiran Berat Janin di Wilayah Kerja Puskesmas Kedaton Kota Bandar Lampung - Desta Stallaza Alifka; Reni Zuraida; Efriyan Imantika; Ratna Dewi Puspita Sari (Majority, 2023)
One of the activities routinely carried out in antenatal care is the measurement of Fundus Uterine Height (FUH) to determine Estimated Fetal Weight (EFW). Fetal weight growth can be indirectly affected by the basic nutritional knowledge of pregnant women about the importance of fulfillinf nutrition during pregnancy to support the health and development of the fetus. The aim of the study was to determine the relation between the level of nutritional knowledge of pregnant women and the estimated fetal weight at Kedaton Primary Health Center Bandar Lampung City. The research design used was analytic observational with cross sectional approach using primary data by measuring the knowledge of pregnant women using a questionnaire consisting of 28 question items and secondary data in the form of uterine fundal height in the KIA book. Sampling was conducted at the Kedaton Primary Health Center in 2020. The sample was taken using purposive sampling with a total sample of 46 samples that met the inclusion and exclusion criteria. Data analysis used Chi Square with α = 0.05 and CI = 95%. The results showed that there were 8.7% mothers with good nutritional knowledge, 71.7% mothers with moderate nutritional knowledge and 19.6% mothers with poor nutrition knowledge. Then pregnant women with small EWF during pregnancy and large EFW during pregnancy consisted of 10.9% and 78.3% respectively of mothers with EFW according to gestational age. Bivariate analysis showed that there was a relationship between the level of nutritional knowledge in pregnant women and the estimated fetal weight at Kedaton Health Center with a value of p = 0.003. There is a correlation between the level of nutritional knowledge of pregnant women with the estimated fetal weight.